Spontaneous remission of chronic lymphocytic leucemia in a patient with SARS-CoV2. (2022) - Bülbül, Hale; Nazlı, Hamza Ekmel; Olgun, Aybüke; Togay, Alper; Kahraman, Dudu Solakoğlu
Highlights: Chronic lymphocytic leukaemia (CLL) is still considered incurable. SARS-CoV2 has the ability to induce injury and death of infected cells and tissues. The main effect of SARS-CoV2 is attributed to hyperactivation of T cells. Cross-reactivity of virus-specific T cells with tumour antigens can lead to regression of tumours. Abstract: Although novel therapies have improved the treatment outcome of patients, chronic lymphocytic leukaemia (CLL) is still considered incurable. Recently, a novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), causing coronavirus disease 2019 (Covid 19), emerged in late 2019, and it has posed a global health threat. In a limited number of cases, it has been shown that some lymphoma types spontaneously regress after SARS-CoV2 infection suggesting that the infection can trigger de immune system against the tumour cell. Cross-reactivity of pathogen-specific T cells with tumour antigens and natural killer cell activation can be the possible mechanism of this hypothesis.